1967
DOI: 10.1172/jci105561
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Sympathetic Nervous System in Regulating Renin and Aldosterone Production in Man *

Abstract: Summary. Several lines of evidence have been developed indicating that the sympathetic nervous system may play a role in mediating the renal and adrenocortical secretary responses to upright posture and sodium deprivation. Despite concurrent increases in arterial blood pressure, the plasma renin activity of normal subjects increased both in response to the infusion of catecholamines (norepinephrine: epinephrine, 10: 1) and in response to stimulation of the sympathetic nervous system by cold. Aldosterone excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
5
2

Year Published

1968
1968
1987
1987

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(105 citation statements)
references
References 25 publications
4
94
5
2
Order By: Relevance
“…in patients with orthostatic hypotension due to other neurological disorders have produced conflicting evidence for the role of the sym pathetic nervous system in renin release. It has been suggested that an integrated sympathetic nervous system is necessary (Gordon, Kuchel, Liddle & Island, 1967;Chokroverty, Barron, Katz, Del Greco & Sharp, 1969) but our present observations fail to support this view. Corbett, Frankel and Harris (1971C) have investigated the cardiovascular responses to change of posture in tetraplegic man and considered that any blood pressure overshoot they observed immediately after return to the supine position was associated with a spasm of skeletal muscles.…”
contrasting
confidence: 99%
“…in patients with orthostatic hypotension due to other neurological disorders have produced conflicting evidence for the role of the sym pathetic nervous system in renin release. It has been suggested that an integrated sympathetic nervous system is necessary (Gordon, Kuchel, Liddle & Island, 1967;Chokroverty, Barron, Katz, Del Greco & Sharp, 1969) but our present observations fail to support this view. Corbett, Frankel and Harris (1971C) have investigated the cardiovascular responses to change of posture in tetraplegic man and considered that any blood pressure overshoot they observed immediately after return to the supine position was associated with a spasm of skeletal muscles.…”
contrasting
confidence: 99%
“…Both in man [11,28] and experimental animals [30,35], renin release has been shown with activation of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…39 Others noted increases in blood levels or secretion rates of aldosterone following the combined stimulus on norepinephrine and epinephrine. 5 ' * Angiotensin II being the major regulator of aldosterone secretion, 40 it is probable that aldosterone activation in our subjects was at least partly due to the concomitant increase in PRA. Nevertheless, the absence of a significant correlation between norepinephrine-induced increases in PRA and those in plasma aldosterone suggest that additional factors may be involved.…”
Section: Discussionmentioning
confidence: 89%